Gut content, feeding behavior, and gut microbiome of Pangasius nasutus (Bleeker, 1863) in natural habitat and captivity environment: A review - Fauzi, Farahin (Iranian Society of Ichthyology, 2023)
Pangasius nasutus is a freshwater fish that has become one of the major economic sources for fish farmers in Pahang River, Malaysia. Effective aquaculture and conservation P. nasutus depend on the understanding of their gut composition, feeding habits, and gut microbiome. Pangasius nasutus in their natural habitat mostly consume a variety of food sources, including zooplankton, aquatic insects, and crustaceans. The advances in metagenomic sequencing technologies have made it possible to examine gut bacteria by examining hypervariable areas of 16S rDNA for prokaryotes and 18S for eukaryotes through cloning and transferring biologically produced DNA into a bacterial host. In recent times, significant attention has been directed towards nutritional manipulation and the modification of gut microbiota to align with the requirements of aquaculture, all the while aiming to preserve the health and welfare of the host. This paper intends to review the gut content and feeding behavior of Pangasius sp. that will be contributed to local fish farmer for their breeding and produce high-quality P. nasutus in a short period of time.